2022
DOI: 10.3389/fneur.2022.919778
|View full text |Cite
|
Sign up to set email alerts
|

Motor- and cognition-related safety of pimavanserin in patients with Parkinson's disease psychosis

Abstract: BackgroundPimavanserin, a selective 5-HT2A inverse agonist/antagonist, is the only treatment approved by the US Food and Drug Administration for hallucinations and delusions associated with Parkinson's disease (PD) psychosis.AimWe aimed to evaluate motor- and cognition-related safety in pimavanserin-treated patients with PD psychosis.MethodsThis analysis included patients with PD psychosis treated with pimavanserin 34 mg from a pooled analysis of 3 randomized, double-blind, placebo-controlled, 6-week studies [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Taken together, 433 patients were included in the pooled analysis. 43 The authors found that pimavanserin was well tolerated without a negative impact on motor-symptoms or cognition. Moreover, a meta-analysis 42 which included four studies comparing 417 patients with PDP treated with pimavanserin versus 263 patients with PDP treated with placebo revealed that the groups had similar scores for Unified Parkinson’s Disease Rating Scale II and III (UPDRS II and III) with a mean difference of 0.09 (95% CI–1.28, 1.46, p = 0.89).…”
Section: Pimavanserinmentioning
confidence: 96%
See 3 more Smart Citations
“…Taken together, 433 patients were included in the pooled analysis. 43 The authors found that pimavanserin was well tolerated without a negative impact on motor-symptoms or cognition. Moreover, a meta-analysis 42 which included four studies comparing 417 patients with PDP treated with pimavanserin versus 263 patients with PDP treated with placebo revealed that the groups had similar scores for Unified Parkinson’s Disease Rating Scale II and III (UPDRS II and III) with a mean difference of 0.09 (95% CI–1.28, 1.46, p = 0.89).…”
Section: Pimavanserinmentioning
confidence: 96%
“…There have been several concerns on pimavanserin’s safety. 43 A retrospective analysis of 2186 pimavanserin users and 18,212 non-users between 2015 and 2018 showed an increased risk of hospitalization at one month of treatment initiation of pimavanserin and a higher risk of death for up to one year following initiation, 44 whereas other studies did not find higher mortality or morbidity rates in pimavanserin users. 45–47 …”
Section: Pimavanserinmentioning
confidence: 98%
See 2 more Smart Citations
“…Notable adverse effects in studies mainly comprised headaches, constipation, edema, hallucinations, and urinary tract infections. Due to QTc prolongation in some patients, additional pharmacovigilance is required (Tariot et al 2021 ; Abler et al 2022 ; Cummings et al 2014 ; Isaacson et al 2021 ). Currently, two phase 4 studies for comparison of treatments with quetiapine or pimavanserin are recruiting in the US (NCT04373317, NCT05590637).…”
Section: Symptomatic Therapymentioning
confidence: 99%